PERANAN SEKRETARIAT DPRD DALAM MENDUKUNG FUNGSI DPRD (STUDI DI SKRETARIAT DPRD KOTA TOMOHON) - RINDENGAN, BRYAN RIZKY; Tulusan, Femmy; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: In accordance with the mandate of Law Number 32 Year 2004 on Regional Governmentand Government Regulation No. 41 of 2007 concerning the regional Organization, that the ParliamentSecretariat is area that has the task to provide services administrative to Parliament, so the ParliamentSecretariat has an important role in supporting implementation of the functions of Parliament. In thisregard, this study to answer the question "What is the role of the Parliament Secretariat in supportingthe implementation of the function of Parliament has been executed effectively and efficiently inTomohon?"Research using qualitative methods. In this case the role of the secretariat of Parliament in favor ofParliament diihat function of two aspects: effectiveness and efficiency. Informants in this study weretaken from the officials and employees of the Parliament Secretariat Tomohon (5) and the Chairmanof Parliament Tomohon (5). Data collection by interview; while the analysis of data using analysistechniques interactive model of Miles and Hubernann.The results showed: (1) The role of the Parliament Secretariat Tomohon in supporting theimplementation of the functions of Parliament are carried out effectively seen from the successfulimplementation of programs and activities that have been set, and the level of realization orachievement of targets planned results. (2) The role of the Parliament Secretariat Tomohon insupporting the implementation of the functions of Parliament are carried out efficiently be seen fromthe use of the budget and the utilization of human potential employees, as well as the degree oftimeliness of implementation and completion of assigned tasks.Based on the results of these studies conclude that the role of the Parliament Secretariat Tomohon insupporting the implementation of the function of Parliament has been done effectively and efficiently.In other words, Parliament Secretariat Tomohon already can act effectively and efficiently insupporting implementation of the functions of Parliament.Based on these results it is suggested some things Tomohon City Council secretariat role in the future:(1) Improving the competence or ability of employee skills through education and technical trainingand functional. (2) Improve the more effective coordination between the Secretariat of the Council andwith the Parliament; (3) Enhance the spirit and enthusiasm of employees working at improving thewelfare of employees.Key Word : Secretariat Role, Parliament